The Dark Side of Expressed Humility for Non-humble Leaders: A Conservation of Resources Perspective - Yang, Kejian; Zhou, Longzhi; Wang, Zhen; Lin, Chen; Luo, Zhengxue (Frontiers in Psychology, 2019)
Although existing studies to date predominately focus on the beneficial effects of leader expressed humility on followers, knowledge about how those behaviors impact the leaders themselves is scarce. Drawing on the conservation of resources theory, we develop and test a model that specifies for whom and how expressing humility has detrimental effects on leaders’ emotional exhaustion and the downstream implications of this effect for leaders’ turnover intentions and work-to-family conflict. Data from a multisource, time-lagged survey of 55 team leaders and 281 followers showed that expressed humility was positively associated with leaders’ emotional exhaustion when Honesty-Humility was low, after controlling for Emotionality, sleep quality, overall job satisfaction and hindrance stressors. In addition, we found that expressed humility was positively and indirectly related to leaders’ turnover intentions and work-to-family conflict via emotional exhaustion when Honesty-Humility was low. Overall, our research sheds light on why and under what conditions the dark side of humble leader behaviors are going to emerge and take their toll on the leaders themselves. Theoretical and practical implications are discussed.